Study of a new piperidone as an anti-Alzheimer agent: Molecular docking, electronic and intermolecular interaction investigations by DFT method - Arulraj Ramalingam (Elsevier, 2021)
In this work, experimental spectroscopic and theoretical methods as quantum chemical calculation were performed for 3-chloro-r(2),c(6)-bis(4-fluorophenyl)-3-methylpiperidin-4-one (abbreviated as CFMP). The CFMP was synthesized and analysed using FT-IR, 1H NMR, 13C NMR, and UV–Vis spectroscopy. Standard functional B3LYP/6–311++G(d,p) density functional theory (DFT) calculations were utilized for the CFMP compound. Molecular electrostatic potential, non-linear optical, and natural bond orbital studies were performed. The charge transfer inside the molecule was demonstrated using HOMO-LUMO energy calculations and Mulliken atomic charges. The vibrational frequency was computed using the DFT/B3LYP/6–311++G(d,p) method. The non-covalent interactions were investigated using the Hirshfeld surface analysis. Furthermore, molecular docking was studied to discover novel inhibitors and drugs in treating Alzheimer's diseases. Further, docking studies were performed to predict and describe the interactions of four proteins with the ligand. This result demonstrates that the CFMP has an inhibitor effect against Alzheimer's diseases.